The Effectiveness of a Training Program Based on Self-Questioning Strategy in Developing Creative Thinking Skills among Tenth Grade Students in Al-Azraq Refugee Camp for Syrians in Jordan - Waed Ihsayian; Rami Alyousef (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This study aimed to examine the effectiveness of a training program based on the strategy of self-questioning in the development of creative thinking skills (originality , flexibility , fluency) among the tenth grade students in Al-Azraq refugee camp in Syria. The study use of Quasi-experimental method and study sample consisted of (40) female students from the tenth grade students for the first semester of the academic year 2018/2019 divided equally in two groups: experimental group and control group. To achieve the objectives of the study were used torrance scale creative thinking after checking its properties psychometric version (1993), which was arabization by (Abu Gado, 2003), and was also a training program from a document application to self-questioning the experimental group strategy. Noting the results of the study the presence of statistically significant differences between the arithmetic averages between the experimental group and the control group was in favor of the experimental group. The study recommended a number of recommendations including the need to benefit from the training program used in the current study through circulation to all primary schools in tenth grade in Syrian refugee camps in Jordan.